Development of Islamic Religious Education Learning Videos in Elementary Schools Using Powtoon Software - Muhammad Ghozil Aulia; Dwi Ratnasari; Mustamid; Lutfina Aribah (Al-Mudarris, 2025)
Islamic Religious Education is an important aspect of the education system. Some Islamic Religious Education teachers are not yet familiar with software that can be used in the teaching and learning process. The learning process still uses conventional learning methods. Therefore, research needs to be conducted to identify software that can be used as an alternative. One software that can be used is Powtoon. Powtoon software can be developed in the form of animated videos containing Islamic Religious Education learning materials. This research uses a 3D model, which consists of the Define, Design, and Development stages. The subjects used in this study were Islamic Religious Education teachers and 5th grade elementary school students. The results showed that the material expert assessment was 94% in the very feasible category. Meanwhile, the media expert assessment showed a score of 81.4% in the very feasible category, and the peer review test showed a score of 91.8% in the very feasible category as well. This shows that the use of Powtoon software can be an alternative for teachers in developing learning media that is interesting for students. In addition, it can help students overcome boredom in learning. The conclusion of this study is that Powtoon software can be utilized by teachers and students in PAI learning.